Cryptographic hardware and embedded systems - CHES 2011 13th International Workshop, Nara, Japan, September 28 - October 1, 2011. Proceedings - Preneel, Bart 1963-; Takagi, Tsuyoshi (Lecture notes in computer science, 2011)
This book constitutes the proceedings of the 13th International Workshop on Cryptographic Hardware and Embedded Systems, CHES 2011, held in Nara, Japan, from September 28 until October 1, 2011. The 32 papers presented together with 1 invited talk were carefully reviewed and selected from 119 submissions. The papers are organized in topical sections named: FPGA implementation; AES; elliptic curve cryptosystems; lattices; side channel attacks; fault attacks; lightweight symmetric algorithms, PUFs; public-key cryptosystems; and hash functions.